PENERAPAN TEKNOLOGI BUDIDAYA RAMAH LINGKUNGAN DAN STRATEGI BRANDING PRODUK BAGI KWT ANGGRAINI DI KABUPATEN DHARMASRAYA : Implementation of Environmentally Sustainable Cultivation and Branding Product to Increase the Capacity of Anggraini Women Farmers Group in Sitiung District, Dharmasraya Regency - Ekawati, Fitri; Hariandi, Doni; Yulistriani, Yulistriani; Mustafa, Muhammad Agil (LPPM Universitas Andalas, 2026)
Environmentally sustainable agriculture has become a critical global issue in addressing climate change, land degradation, and food security challenges. However, at the smallholder level, its implementation remains constrained by limited knowledge, skills, and market access. This community service program aimed to: (1) improve the capacity of members of the Anggraini Women Farmers Group (KWT) in producing environmentally friendly agricultural inputs; (2) increase the adoption of sustainable cultivation practices; and (3) enhance product value through branding. The program was conducted over six months using a participatory community empowerment approach involving 15 group members. The methods included training, demonstrations, hands-on practice, and continuous mentoring. Evaluation was carried out using pre-test and post-test assessments and Likert-scale questionnaires. The results showed significant improvements across all indicators. Knowledge of environmentally sustainable cultivation increased from 20% to 100%, while skills in producing organic fertilizers and botanical pesticides improved from 30% to 80%. The ability to manage crop cultivation from planting to harvest increased from 50% to 100%. In addition, understanding of product branding increased from 10% to 100%, and promotion skills improved from 10% to 80%. The participant satisfaction level reached a score of 4.8, indicating high relevance and effectiveness of the program. This study demonstrates that an integrated approach combining technical training and marketing strengthening based on local resources is effective in improving farmer capacity and independence. The program has strong potential for replication to support sustainable agriculture development and enhance the economic value of smallholder farming groups.